Strength Evaluation of Flexible Securing Systems for Ship's Deck-Stowed Containers - Vea, Reynaldo B. (Philippine Engineering Journal; Vol 5 No 2 (1984), 2021)
The seaway forces acting on ship’s on-deck containers, the elements of strength of containers and their securing gear and equations characterizing the behavior of flexible securing systems are discussed. An algorithm that generates points for a container stack weight diagram, for use by ship deck officers, is presented.